2022
DOI: 10.5946/ce.2022.037
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators in colonoscopy: the chasm between ideal and reality

Abstract: Continuous measurement of quality indicators (QIs) should be a routine part of colonoscopy, as a wide variation still exists in the performance and quality levels of colonoscopy in Korea. Among the many QIs of colonoscopy, the adenoma detection rate, average withdrawal time, bowel preparation adequacy, and cecal intubation rate should be monitored in daily clinical practice to improve the quality of the procedure. The adenoma detection rate is the best indicator of the quality of colonoscopy; however, it has m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The “quality of bowel preparation” is defined as the degree of visualization of the colonic mucosa during colonoscopy, which may also be referred to as the “bowel cleanliness” or “bowel cleansing” (Park & Cha, 2022). In this systematic review, the quality of bowel preparation was the primary outcome used to assess the efficacy of the exercise therapy on bowel preparation.…”
Section: Resultsmentioning
confidence: 99%
“…The “quality of bowel preparation” is defined as the degree of visualization of the colonic mucosa during colonoscopy, which may also be referred to as the “bowel cleanliness” or “bowel cleansing” (Park & Cha, 2022). In this systematic review, the quality of bowel preparation was the primary outcome used to assess the efficacy of the exercise therapy on bowel preparation.…”
Section: Resultsmentioning
confidence: 99%
“…32,33 These high numbers suggest that a gap still exists between the target bowel preparation quality and actual colonoscopy performance. 34 This gap can be narrowed when documentation of bowel preparation with the BBPS becomes a routine part of a colonoscopy. As a result, bowel preparation quality should be a priority indicator for colonoscopy, and good documentation is essential to avoid litigation and reimbursement issues.…”
Section: Bowel Preparation Qualitymentioning
confidence: 99%
“…Despite repeating colonoscopies due to inadequate bowel preparation being costly and increasing the burden on patients and physicians, several studies have shown that rates of inadequate bowel preparation continue to range from 20% to 25% in multiple centers 32,33 . These high numbers suggest that a gap still exists between the target bowel preparation quality and actual colonoscopy performance 34 . This gap can be narrowed when documentation of bowel preparation with the BBPS becomes a routine part of a colonoscopy.…”
Section: Bowel Preparation Qualitymentioning
confidence: 99%
“…We reviewed the latest literature, mainly randomized controlled trials (RCTs) or meta-analyses published in the past five years, and showed the effectiveness of IEE in terms of adenoma detection rate (ADR) and polyp detection rate (PDR), which are established quality indicators in colonoscopy. 17 - 19 The features of each IEE and the representative studies are summarized in Tables 1 and 2 , respectively. 20 - 24 …”
Section: Introductionmentioning
confidence: 99%
“…15,16 We reviewed the latest literature, mainly randomized controlled trials (RCTs) or meta-analyses published in the past five years, and showed the effectiveness of IEE in terms of adenoma detection rate (ADR) and polyp detection rate (PDR), which are established quality indicators in colonoscopy. [17][18][19] The features of each IEE and the representative studies are summarized in Tables 1 and 2, respectively. [20][21][22][23][24] NARROW-BAND IMAGING NBI was developed by Olympus Corporation and emphasizes the microstructure and capillaries on the mucosal surface by modifying the center wavelength and bandwidth of light into narrow-band illumination at 415±30 nm within the hemoglobin absorption band.…”
mentioning
confidence: 99%